PENERAPAN MODEL EVERYONE IS A TEACHER HERE UNTUK MENINGKATKAN KEMAMPUAN PROBLEM SOLVING DAN HASIL BELAJAR PADA PENDIDIKAN AGAMA - Lumban Gaol, Rina Martasari; Ermina Waruwu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve students’ Problem Solving skills and learning outcomes in Phase F Class XI-1 of Catholic Religious Education through the implementation of the Everyone Is a Teacher Here (EITH) learning model at Santo Yoseph Private Senior High School Medan. The study was motivated by students’ low ability to identify problems, gather information, analyze problems, formulate alternative solutions, select the best solution, implement solutions, and conduct evaluations. This research employed a Classroom Action Research (CAR) method conducted in two cycles consisting of planning, action, observation, and reflection stages, involving 38 students as the research subjects. Data were collected through observation, learning outcome tests, and documentation. The results showed that the implementation of the Everyone Is a Teacher Here learning model contributed to the improvement of students’ Problem Solving skills and learning outcomes. The average Problem Solving score increased from 69 in the pre-action stage to 80 in Cycle I and further increased to 89 in Cycle II. Students’ learning outcomes also improved from an average score of 84 in Cycle I to 91 in Cycle II. This improvement was supported by students’ active participation in asking questions, engaging in discussions, answering questions, and expressing opinions during the learning process. The findings indicate that the Everyone Is a Teacher Here learning model can serve as an alternative active learning approach to enhance students’ Problem Solving skills and learning outcomes in Catholic Religious Education.